CALCULATION OF SOIL WATER DIFFUSIVITY USING A MODEL FOR SOIL MOISTURE PROFILE UNDER DIFFERENT SALINITY CONDITIONS - Mahdi I. Aoda; Taghreed F. Younan (Journal of Engineering, 2010)
A closed formed model modified from that of van Genuchten (1980) was used to fit the data of soil moisture profile ( θ vs. λ ) from which the slope dλ/dθ can be evaluated and then the soil water diffusivity [D(θ)] can be calculated. Diffusivity was calculated for three soil textures under different salinity conditions. The results showed that the model fitted the data very well with 1% confidence level (R2 > 0.93). D(θ) increased sharply with soil moisture for all soils but its values were lower when the texture got finer. At a certain sodium adsorption ratio (SAR), D(θ) increase with the increase of salt concentration (C) of the water infiltrating. Increasing SAR of water caused a decrease in D(θ) at any level of C. Same trends were obtained for the values of weighted mean diffusivity D .